Penggunaan muzik dalam pembelajaran dan pengajaran kerja amali kemahiran hidup sekolah rendah - Salim, Hamisan (2010)
The goal of this study is to ascertain whether music applied in the learning and teaching process could positively enhance and influence the interests and readiness of the students towards life skills subject hence inculcate good learning practices by the students one of the primary national type school in Pontian District, Johor. This study samples comprise of 180 year 4,5 and 6 students of that particular school. It is a handson observation of the learning and teaching process of life skills subject in its workshop. Through-out this study, stratified Proportional Random Technique is utilised and all the data gathered will be analysed using the SPSS programme (Packages for Social Science). Statisfical mean and standard deviation and 0.05 tolerance is used to describe and transcribe all the data. There are four problems statement which addreses the issue of how much music could influence the interests of the students towards the life skills subject is found as 4.35. Whereas the second statement which explores the students’ perception towards learning of life skills subject subjected music arousal is 4.51. The subsequent statement determine the readiness of the students to learn life skills subject enhanced with music is found to be 4.27. Last but not least the meant of the effect of learning life skills subject influenced with music to achieve high productivity and knowledge retention as 4.78. It is observed that all the issues raised in the problem statements rendered a high reading which give a connotation of a positive meaningful and high reception of the subjects learned by the students. As a conclusions, this study shows that majority of the respondents agree to the nation that music can be used in the learning and teaching process of life skills subject in the primary school.